Use of resterilized polypropylene mesh in inguinal hernia repair: A prospective, randomized study - GÜLLÜOĞLU, MAHMUT BAHADIR (ELSEVIER SCIENCE INC, 2005)
BACKGROUND: Inguinal hernia repair consumes considerable health-care resources worldwide. Open mesh repairs are commonly used and the feasibility of using a resterilized mesh, which is a general practice in certain countries, has not been evaluated. STUDY DESIGN: In this randomized prospective study, original and resterilized meshes were used in two groups of patients with unilateral inguinal hernia. Microbiologic changes, textile mechanical properties, overall complication rates, and cost-effectiveness of resterilized mesh were investigated. A time period of 3 years was determined for patient enrollment to this pilot feasibility study, with the goal of 100 patients in each group. RESULTS: Ninety-one patients were enrolled in the original group and 93 in the resterilized mesh group. Median followup was 735 and 739 days and calculated interquartile ranges were 454 and 513 days, respectively. Average tensile strength of the original polypropylene mesh changed slightly with resterilization, as maximum load decreased from a mean of 66.6 to 58.2 N/cm. Overall complication rates were similar in the two groups. The 6.6% infection rate in the original mesh group was not statistically different from the 7.5% rate in the resterilized group (p = 0.80, relative risk = 0.88, 95% confidence interval, 0.31-2.51). There was only one recurrence in the original mesh group in the 21(st) month. Use of a resterilized mesh decreased the overall cost of operation by decreasing the cost of mesh from 15.9% to 8.3% of the total amount. CONCLUSIONS: Use of a resterilized mesh for inguinal hernia repair is feasible without considerable changes in infection and recurrence rates.
Keywords: SURGICAL SITE INFECTION; TENSION